2022
DOI: 10.1097/cm9.0000000000002028
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring for the management of hypertension

Abstract: Ambulatory blood pressure monitoring (ABPM) has become indispensable in the current management of hypertension. ABPM is particularly useful in the accurate diagnosis of hypertension. Its diagnostic thresholds had been recently established based on hard clinical outcomes. Cross-classification of patients according to office and ambulatory blood pressure identifies white-coat, masked, and sustained hypertension. ABPM is also useful in cardiovascular (CV) risk assessment. It provides information on daytime and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…BP exhibits a circadian rhythm, with a decline during sleep and a gradual increase upon awakening. 86 In 1988, O'Brien et al 87 reported that individuals with a mean diurnal BP difference of less than 10 or 5 mm Hg had a history of recurrent stroke; these individuals are referred to as non-dippers. 87 Normally, blood pressure decreases by approximately 10%–20% during the night compared to daytime levels, which defines the dipper pattern.…”
Section: The Impact Of Individual Variations On the Accuracy Of Blood...mentioning
confidence: 99%
“…BP exhibits a circadian rhythm, with a decline during sleep and a gradual increase upon awakening. 86 In 1988, O'Brien et al 87 reported that individuals with a mean diurnal BP difference of less than 10 or 5 mm Hg had a history of recurrent stroke; these individuals are referred to as non-dippers. 87 Normally, blood pressure decreases by approximately 10%–20% during the night compared to daytime levels, which defines the dipper pattern.…”
Section: The Impact Of Individual Variations On the Accuracy Of Blood...mentioning
confidence: 99%